The Effect of Good Governance on The Financial Statements Quality - Nirwana; Darmawaty (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to analyze the effect of good governance on the quality of financial reports. This research was carried out in the vertical agency of the Ministry of Agriculture in the South Sulawesi Region using the survey method. The instrument in this study was in the form of a questionnaire. In this study, the sample used is 74 which is a saturated sample from the finance department, commitment making officials, procurement officials and goods managers in each work unit. The method used in this study is quantitative using a simple linear regression analysis tool. In conducting simple linear regression testing, this study uses the help of the SPSS (Statistical Package for the Social Sciences) application version 21. The results of this study indicate that good governance has an effect on the quality of financial reports.